Positive electrode active material and lithium ion battery
A lithium nickel cobalt manganese oxide-based positive electrode active material with controlled molar ratios and additive elements stabilizes the crystal structure, addressing the issue of metal elution and enhancing charging capacity and safety in lithium-ion batteries.
Patent Information
- Application Number
- JP2024529686
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-12-01
- Filing Date
- 2022-12-16
- Publication Date
- 2025-01-17
AI Technical Summary
The challenge of improving the charging speed and stability of lithium-ion batteries is hindered by the elution of transition metals from the positive electrode active material, which affects the charging capacity, cycle life, and safety performance.
A lithium nickel cobalt manganese oxide-based positive electrode active material is formulated with controlled molar ratios of nickel, cobalt, and manganese, along with the addition of elements like Zr, Al, and others, to stabilize the crystal structure and reduce metal elution, ensuring uniform particle size and appropriate peak ratios for enhanced performance.
The solution results in improved charging capacity, extended cycle life, and enhanced safety performance by minimizing metal elution and structural instability, thereby optimizing the battery's performance under fast-charging conditions.
Smart Images

Figure 2025501057000001 
Figure 2025501057000002 
Figure 2025501057000003
Abstract
Description
CROSS-REFERENCE TO RELATED APPLICATIONS
[0001] The present invention claims priority to Chinese Patent Application No. 202211523409.2, entitled "Positive Electrode Active Material and Lithium Ion Battery", filed on December 1, 2022 by the applicant, Xinwangda Electric Vehicle Battery Co., Ltd., the entire contents of which are incorporated herein by reference. [Technical field]
[0002] The present invention relates to a positive electrode active material and a lithium ion battery, and belongs to the technical field of secondary batteries. [Background technology]
[0003] In recent years, as the environmental problems caused by traditional fuel vehicles become more and more prominent, people urgently need environmentally friendly, low-carbon and sustainable alternative energy for automobiles. As a kind of clean energy, secondary batteries, such as lithium-ion batteries, have high energy density and long life, and have been widely used in recent years. Compared with traditional fuel vehicles, new energy vehicles powered by lithium-ion batteries need to replenish energy by charging the lithium-ion batteries, so the charging time has a direct impact on the user experience of the new energy vehicles. Therefore, improving the charging speed of secondary batteries has always been an important research direction in the new energy industry. Summary of the Invention
[0004] The present invention aims to provide a positive electrode active material, and a lithium ion battery produced using the positive electrode active material can reduce the elution of transition metals from the positive electrode active material in the lithium ion battery, reduce slip cracks and interactions between the interface and the electrolyte, and improve the charging capacity, cycle life, and safety performance of the secondary battery.
[0005] The positive electrode active material according to the present invention contains lithium nickel cobalt manganese oxide, In lithium nickel cobalt manganese oxide, when the total molar amount of nickel element, cobalt element and manganese element is 100%, the molar amount of manganese element is m%, the molar amount of cobalt element is n%, 20 < n + m < 50, and 0.1 < n / m < 0.6 are satisfied. Let the full width at half maximum of the (003) peak of the positive electrode active material be FWHW(003), and the full width at half maximum of the (104) peak of the positive electrode active material be FWHW(104). FWHW(003) and FWHW(104) satisfy 0.4 ≦ FWHW(003) / FWHW(104) ≦ 2.0.
[0006] Furthermore, the molar contents of manganese element and cobalt element are (i) 19 ≦ m < 43.5, (ii) 3.0 ≦ n ≦ 12, and (iii) satisfy any one of 0.10 ≦ n / m ≦ 0.502.
[0007] Furthermore, the positive electrode active material further contains an M element, and the M element contains Zr and at least one of Al, Mg, Ti, Y, Sr, Y, Mo, Nb, Sn, Ba, La, Ce elements. When the total amount of nickel element, cobalt element and manganese element is 100%, the percentage of the molar amount of the M element to the total molar amount of nickel element, cobalt element and manganese element is x%, and 0.1 ≦ x ≦ 2.5.
[0008] Moreover, the M element contains Zr element and at least one of Al element and Mg, Ti, Y, Sr, Y, Mo, Nb, Sn, Ba, La, Ce, W elements. Let the molar content of the M element be x%, the molar content of Zr be x1%, and the molar content of Al be x2%. x, x1 and x2 are (iv) 0.20 ≦ x1 ≦ 0.45, (v) 0.15 ≦ x2 ≦ 1.5, (vi) 0.2 ≦ x1 / x2 ≦ 1, and (vii) satisfy any one of 0 < (x - x1 - x2) / x < 0.5.
[0009] Let the full width at half maximum of the (003) peak of the positive electrode active material of the present invention be FWHW(003), and the full width at half maximum of the (104) peak of the positive electrode active material be FWHW(104). The range of FWHW(003) is 0.06° to 0.15°. The range of FWHW(104) is 0.06° to 0.15°.
[0010] Let the peak area of the (003) peak of the positive electrode active material of the present invention be Ic(003), the peak area of the (104) peak be Ic(104), Kc is Ic(003) / Ic(104), and 1 ≤ Kc ≤ 2.
[0011] The positive electrode active material of the present invention contains Li a Ni b Co m / 100 Mn n / 100 M x / 100 O2, where 0.80 ≤ a ≤ 1.10, 0.4 < b < 0.8, 20 < n + m < 50, 0.1 < n / m < 0.6, 0.1 ≤ x ≤ 2.5, and M contains Zr and at least one of Al, Mg, Ti, Y, Sr, Y, Mo, Nb, Sn, Ba, La, Ce, and W.
[0012] Based on the positive electrode active material, the secondary battery according to the present invention includes a positive electrode. The positive electrode includes a positive electrode current collector and a positive electrode mixture layer provided on the positive electrode current collector. The positive electrode mixture layer is composed of the positive electrode active material. Let the peak area of the (003) peak of the positive electrode mixture layer be If(003), the peak area of the (104) peak be If(104), Kf is If(003) / If(104), 10 ≤ Kf ≤ 20, and 6 ≤ Kf / Kc ≤ 20.
[0013] The ratio of the number of particles with a size of 1 μm to 3 μm formed by the positive electrode active material in the positive electrode mixture layer to the total number of particles is greater than 60%. The uniformity of the size of the positive electrode active material particles in the positive electrode mixture layer significantly affects the charging performance of the battery. The more uniform the size of the positive electrode active material particles in the positive electrode mixture layer, the smaller the difference in current density under high-current charging conditions between different active particles of the positive electrode active material, that is, the degree of lithium deintercalation between different particles is consistent, indicating that polarization is reduced. Furthermore, the rate of increase in the battery temperature decreases, ensuring that the battery has excellent charging capacity and service life.
Mode for Carrying Out the Invention
[0014] The experimental methods used in the following embodiments are all conventional methods unless otherwise specified.
[0015] The materials, reagents, etc. used in the following embodiments are all commercially available unless otherwise specified.
[0016] The positive electrode active material according to the present invention contains lithium nickel cobalt manganese oxide. In lithium nickel cobalt manganese oxide, assuming the total molar amount of nickel element, cobalt element and manganese element is 100%, the molar amount of manganese element is m%, and the molar amount of cobalt element is n%, satisfying 20 < n + m < 50 and 0.1 < n / m < 0.6. Let the full width at half maximum of the (003) peak of the positive electrode active material be FWHW(003), and the full width at half maximum of the (104) peak of the positive electrode active material be FWHW(104). FWHW(003) and FWHW(104) satisfy 0.4 ≦ FWHW(003) / FWHW(104) ≦ 2.0. For example, the value of FWHW(003) / FWHW(104) may be any value among 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 0.99, 1.0, 1.1, 1.3, 1.5, 1.8, 2.0 or a range consisting of any two of these values.
[0017] In some embodiments of the present invention, 22 < n + m < 48 and 0.103 < n / m < 0.502.
[0018] In some embodiments of the present invention, FWHW(003) is the half-width of the (003) peak of the positive electrode active material, and FWHW(104) is the half-width of the (104) peak of the positive electrode active material, and 0.4≦FWHW(003) / FWHW(104)≦1.5. When FWHW(003) / FWHW(104) of the positive electrode active material is in the above range, the stability of the crystal structure of the positive electrode active material is high, and the charging ability, cycle life, and safety performance of the secondary battery can be improved. In some embodiments of the present invention, 0.5≦FWHW(003) / FWHW(104)<1. When FWHW(003) / FWHW(104) is in the above range, it indicates that the residual stress inside the lattice of the positive electrode active material particles is low or the mixing rate of lithium ions and transition metal ions is low, and the residual stress inside the lattice or ion mixing causes the atoms in the lattice to shift from their equilibrium positions, resulting in a certain value of FWHW(003) or FWHW(104) being high and the ratio of FWHW(003) / FWHW(104) changing. The residual stress inside the lattice or ion mixing increases the barrier for lithium ions to desorb from the positive electrode active material, resulting in a decrease in the charging ability of the battery.
[0019] In the above positive electrode active material, the manganese element and the cobalt element can stabilize the structural stability of the lithium nickel cobalt manganese oxide in the delithiation process, and have a supporting effect on the material structure. If the manganese element and the cobalt element are too much, the ratio of the nickel element involved in the electrochemical reaction will decrease, and the energy density of the lithium nickel cobalt manganese oxide will further decrease. The nickel element and the manganese element will move to the tetrahedral vacancy in the lattice during the charging process, causing distortion in the lattice of the positive electrode active material, which is easy to damage the stability of the lattice of the material. The nickel ions and manganese ions in the tetrahedral vacancy will also move to the electrolyte and dissolve under the action of the electric field, and the dissolved nickel ions and manganese ions (especially the manganese ions) will be reduced at the negative electrode, which is easy to destroy the surface protective film of the negative electrode, which will lead to an increase in impedance, increase the risk of lithium precipitation, and reduce the charging ability, cycle life and safety performance of the battery. The presence of cobalt element in the positive electrode active material can inhibit the movement of nickel ions and manganese ions into the tetrahedral vacancies in the lattice during charging, but a high content of cobalt will lead to a decrease in the capacity of the positive electrode active material, and cobalt element is a rare metal in the earth's crust, so a high content of cobalt element will increase the cost of the positive electrode active material. By controlling the content of nickel, cobalt, and manganese elements and the stability of the crystal of the formed positive electrode active material, the above problems can be effectively improved.
[0020] In some embodiments of the invention, 19≦m<43.5. For example, m may be any value of 19, 20, 21, 23, 25, 27, 27.5, 28, 30, 32, 33, 34, 37, 39, 40, 42, 43.5, or a range consisting of any two of these values.
[0021] In some embodiments of the invention, 20≦m≦33.
[0022] In some embodiments of the present invention, 20≦m≦30. When m is in the above range, the crystal structure of the positive electrode active material can be further optimized to make the positive electrode active material more stable.
[0023] In some embodiments of the invention, 3≦n≦12. For example, n can be any value of 3, 4.5, 5, 7, 8, 9, 10, 11, 12, 14, or a range consisting of any two of these values.
[0024] In some embodiments of the invention, 4.5≦n≦9.
[0025] In some embodiments of the present invention, 0.10≦n / m≦0.502. For example, n / m may be any value selected from the group consisting of 0.10, 0.15, 0.18, 0.20, 0.22, 0.25, 0.28, 0.30, 0.32, 0.35, 0.38, 0.40, 0.42, 0.45, 0.48, and 0.502, or a range value consisting of any two values selected from the group consisting of 0.10, 0.15, 0.18, 0.20, 0.22, 0.25, 0.28, 0.30, 0.32, 0.35, 0.38, 0.40, 0.42, 0.45, 0.48, and 0.502. When n / m is in this range, the crystal structure of the positive electrode active material can be further controlled, and the performance of the secondary battery is better.
[0026] In some embodiments of the invention, 0.15≦n / m≦0.35.
[0027] In some embodiments of the present invention, the positive electrode active material further comprises an M element, and the M element comprises at least one of Zr, Al, Mg, Ti, Y, Sr, Y, Mo, Nb, Sn, Ba, La, Ce, and W. A suitable M element can form a chemical bond with oxygen in the lithium nickel cobalt manganese oxide and improve the stability with the metal oxygen octahedral structure in the lithium nickel cobalt manganese oxide. At the same time, it reduces the precipitation of transition metals in the negative plate and the release of lattice oxygen in the positive electrode active material, which may cause safety risks, during fast charging.
[0028] In some embodiments of the present invention, the M element includes Zr element and at least one of Al, Mg, Ti, Y, Sr, Y, Mo, Nb, Sn, Ba, La, and Ce elements. The bond energy of the chemical bond formed by Zr element and oxygen is much larger than the chemical energy of the chemical bond formed by nickel, cobalt, and manganese elements and oxygen, so adding M element including Zr can further improve the structural stability of the metal oxygen octahedron in the lithium nickel cobalt manganese oxide.
[0029] In some embodiments of the present invention, the M element includes a W element and at least one of Zr, Al, Mg, Ti, Y, Sr, Y, Mo, Nb, Sn, Ba, La, and Ce elements.
[0030] In some embodiments of the present invention, the M element includes Zr, Al, and at least one of Mg, Ti, Y, Sr, Y, Mo, Nb, Sn, Ba, La, Ce, and W. The bond energy of the chemical bond formed between oxygen and Al in the lithium nickel cobalt manganese oxide in the positive electrode active material is smaller than the bond energy of the chemical bond formed between Zr and Al, but when the Al forms a chemical bond with Zr, it improves the migration energy of nickel ions to the lattice lithium sites in the lithium nickel cobalt manganese oxide, reduces the ratio of nickel ions located in the lattice lithium sites, improves the migration speed of lithium ions, and is advantageous in further improving the charging ability of the battery.
[0031] In some embodiments of the present invention, the M element includes a Zr element, a W element, and at least one of Al, Mg, Ti, Y, Sr, Y, Mo, Nb, Sn, Ba, La, and Ce elements.
[0032] In some embodiments of the present invention, the molar amount of the M element is x%, where the molar amount of the nickel element, the cobalt element and the manganese element is 100%, and the ratio of the molar amount of the M element to the molar amount of the nickel element, the cobalt element and the manganese element is 0.1≦x≦2.5. For example, x may be any value among 0.1, 0.3, 0.5, 0.7, 0.9, 1.0, 1.1, 1.3, 1.5, 1.7, 1.9, 2.0, 2.2, 2.4, 2.5, or a range consisting of any two values among them. By adjusting the content of the M element, it is possible to effectively reduce the dissolution of metal and the release of lattice oxygen, and further improve the charging ability, service life and safety performance of the battery.
[0033] In some embodiments of the present invention, 0.2≦x≦1.5. When the battery is charged quickly, the lithium nickel cobalt manganese oxide will cause the elution of transition metals nickel and manganese, resulting in a decrease in the structural stability of the positive electrode active material and destruction of the surface protective film of the negative electrode plate, thereby reducing the charging ability and service life of the battery. The precipitation of transition metals on the negative electrode side and the release of lattice oxygen will lead to safety risks. When the content of M element is within the above range, the structural stability of the positive electrode active material can be guaranteed, and the impact on the available capacity of the positive electrode active material can be reduced, so that the battery can achieve high capacity, excellent charging ability, service life and safety performance at the same time.
[0034] In some embodiments of the present invention, the M element includes Zr, Al, and at least one of Mg, Ti, Y, Sr, Y, Mo, Nb, Sn, Ba, La, Ce, and W, and the molar content of the M element is x%, the molar content of Zr is x1%, and the molar content of Al is x2%.
[0035] In some embodiments of the present invention, 0.20≦x1≦0.45. For example, x1 may be any value among 0.20, 0.22, 0.24, 0.25, 0.27, 0.29, 0.30, 0.32, 0.34, 0.36, 0.39, 0.40, 0.42, 0.44, 0.45, or any two values among them. The addition of Zr element can effectively reduce the dissolution of metal and the release of lattice oxygen, and improve the charging ability, service life, and safety performance of the battery.
[0036] In some embodiments of the present invention, 0.24≦x1≦0.42.
[0037] In some embodiments of the present invention, 0.15≦x2≦1.5. For example, x2 may be any value of 0.15, 0.20, 0.25, 0.3, 0.32, 0.35, 0.37, 0.40, 0.45, 0.47, 0.50, 0.53, 0.57, 0.59, 0.60, 0, 63, 0.65, 0.68, 0.70, 0.73, 0.75, 0.78, 0.80, 0.85, 0.90, 0.93, 0.95, 1.0, 1.2, 1.5, or any two of them. By controlling the addition of the Al element, it is possible to effectively reduce the dissolution of metal and the release of lattice oxygen, and improve the charging ability, service life, and safety performance of the battery.
[0038] In some embodiments of the invention, 0.25≦x2≦1.2.
[0039] In some embodiments of the invention, 0.3≦x2≦0.95.
[0040] In some embodiments of the present invention, 0.2≦x1 / x2≦1. For example, x1 / x2 may be any value selected from 0.20, 0.25, 0.3, 0.32, 0.35, 0.37, 0.40, 0.45, 0.47, 0.50, 0.53, 0.57, 0.59, 0.60, 0, 63, 0.65, 0.68, 0.70, 0.73, 0.75, 0.78, 0.80, 0.85, 0.90, 0.93, 0.95, 1.0, or a range value selected from any two of these values. When the content of Al element is equal to or greater than the content of Zr element and the ratio of the two is controlled to be within the above range, the ratio of lattice lithium in the positive electrode active material and the stability of the crystal structure can be improved, the crystal structure of the positive electrode active material can be made more excellent, and the performance of the entire battery can be further improved.
[0041] In some embodiments of the present invention, 0<(x-x1-x2) / x<0.5. For example, (x-x1-x2) / x may be any value among 0.001, 0.05, 0.1, 0.13, 0.15, 0.18, 0.20, 0.25, 0.3, 0.32, 0.35, 0.37, 0.40, 0.45, 0.47, 0.50, or a range value consisting of any two of them. When M element includes Al element, Zr element, and further includes other elements, and the content is within the above range, the crystal structure of the positive electrode active material can be further optimized, and the battery can have better overall performance.
[0042] In some embodiments of the present invention, 0.1≦(x−x1−x2) / x≦0.42. When the above range is satisfied, the overall performance of the positive electrode active material is more excellent.
[0043] In some embodiments of the present invention, the half width of the (003) peak of the positive electrode active material is defined as FWHW(003), and the range of the FWHW(003) is 0.06° to 0.15°. For example, the FWHW(003) may be any value of 0.06°, 0.07°, 0.09°, 0.10°, 0.12°, 0.14°, or 0.15°, or a range consisting of any two of these values.
[0044] In some embodiments of the present invention, the half width of the (104) peak of the positive electrode active material is defined as FWHW(104), and the range of the FWHW(104) is 0.06° to 0.15°. For example, the FWHW(104) may be any value of 0.06°, 0.07°, 0.09°, 0.10°, 0.12°, 0.14°, and 0.15°, or a range consisting of any two of these values.
[0045] The half-width FWHW of the characteristic peak of the positive electrode active material represents the peak width at the position of half the height of the characteristic peak after subtracting the background and Kα2 of the XRD curve, and the unit is °. The scanning speed of XRD is 2° / min. When the half-width FWHM of the (003) characteristic peak and the (104) characteristic peak is less than 0.15°, it indicates that the crystal type of the positive electrode active material is perfect and has high crystallinity, and when the half-width FWHM of the (003) characteristic peak and the (104) characteristic peak is greater than 0.15°, it indicates that the positions of some atoms in the positive electrode active material are deviated from the ideal positions of the crystal, indicating that the crystallinity of the material is low and affecting the service life of the material. However, when the half-width FWHM is less than 0.06°, it indicates that the positive electrode active material is not only highly crystalline but also has a large crystal grain size. When the crystal grain size is large, the movement distance of lithium ions in the bulk phase of the positive electrode active material during the charging process becomes longer, leading to a decrease in the charging ability of the battery. Therefore, it is preferable that the half-width of the (003) characteristic peak and the half-width of the (104) characteristic peak of the positive electrode active material are in an appropriate range, which can ensure that the battery has excellent service life and charging ability.
[0046] In some embodiments of the present invention, the range of the FWHW(003) is 0.07° to 0.098°.
[0047] In some embodiments of the present invention, the range of the FWHW(003) is 0.09° to 0.12°.
[0048] In some embodiments of the present invention, the peak area of the (003) peak of the positive electrode active material is Ic(003), the peak area of the (104) peak is Ic(104), and Kc is Ic(003) / Ic(104), where 1≦Kc≦2. For example, Kc may be any value of 1, 1.1, 1.2, 1.3, 1.35, 1.4, 1.45, 1.48, 1.5, 1.52, 1.54, 1.56, 1.58, 1.6, 1.63, 1.65, 1.67, 1.7, 1.73, 1.75, 1.78, 1.8, 1.85, 1.9, and 2.0, or a range consisting of any two of these values.
[0049] Kc can indicate the crystallinity of the positive electrode active material, and when the Kc value of the positive electrode active material is 1.0 to 2.0, it indicates that the positive electrode active material has high crystallinity and few defects inside the material. When Kc is less than 1.0, the positive electrode active material has low crystallinity and has many defects inside, which may affect the structural stability of the positive electrode active material, resulting in low battery capacity during use and inhibiting the desorption of lithium ions, which may affect the fast charging ability and long life of the material.
[0050] In some embodiments of the invention, 1.3≦Kc≦1.7.
[0051] The positive electrode active material of the present invention can be produced by the following method.
[0052] 1) Precursor Ni b Co m / 100 Mn n / 100 (OH)2, a lithium salt, and an additive A1 containing an additive metal element M1 are placed in a mixer and mixed thoroughly to separate the lithium in the lithium salt and the ternary material precursor Ni b Co m / 100 Mn n / 100The ratio of (OH)2 is a, and 1.95≦a≦1.2, and the lithium salt may be lithium carbonate, lithium hydroxide, or other compounds that can provide lithium element. M1 can be selected from one or more of Mg, Al, Ti, Y, Sr, Zr, Mo, Nb, Sn, Ba, La, Ce, and M1 includes at least Zr element, and additive A1 is an oxide, hydroxide, or other compound that includes additive element M1.
[0053] 2) The mixed material is placed in a sagger and sintered in an atmospheric furnace, with the temperature in the heating region being 25°C to 950°C, the sintering temperature in the constant temperature region being 800°C to 1000°C, the total sintering time in the heating region and the constant temperature region being 15 to 40 hours, pure oxygen is introduced during the sintering process, and the oxygen concentration in the furnace is 20% to 99%. By controlling the amount of positive electrode active material filled in the sagger, the heating rate in the heating region, the sintering temperature in the heating region and the sintering temperature in the constant temperature region, as well as the time and atmosphere, it is possible to control the ratio Kc of the characteristic peak Ic(003) / Ic(104) of the positive electrode active material, the half-width of the (003) characteristic peak and the half-width of the (104) characteristic peak of the positive electrode active material, and the ratio of the half-width of the (003) characteristic peak and the half-width of the (104) characteristic peak of the positive electrode active material, and the size and uniformity of the positive electrode active material particles.
[0054] 3) The positive electrode active material obtained after sintering is subjected to roller crushing and airflow crushing, and the size distribution of the positive electrode active material particles can be controlled by controlling the parameters of the airflow crushing, such as the diameter of the air supply nozzle, the frequency of the material feeder, the frequency of the induction fan, the air pressure, and the weight of the material in the bin.
[0055] 4) The ground positive electrode active material and additive A2 containing additive element M2 are placed in a mixer and thoroughly mixed, where M2 can be selected from one or more of Mg, Al, Ti, Y, Sr, Zr, Mo, Nb, Sn, Ba, La, and Ce, and additive A2 is an oxide, hydroxide, or other compound containing additive element M2.
[0056] 5) The homogeneously mixed mixture of the positive electrode active material and additives is put into a kiln for secondary sintering to obtain the finished positive electrode active material. The sintering temperature is 350℃~850℃, and the sintering time is 5~20 hours. The secondary sintering can repair the surface of the positive electrode particles destroyed during the crushing process, reduce the residual alkali of the material, and form a protective layer with a certain thickness on the surface.
[0057] Based on the above positive electrode active material, a secondary battery according to the present invention includes a positive electrode, the positive electrode including a positive electrode current collector and a positive electrode mixture layer provided on the positive electrode current collector, the positive electrode mixture layer being made of the above positive electrode active material, and in some embodiments of the present invention, the peak area of the (003) peak of the positive electrode mixture layer is If(003), the peak area of the (104) peak is If(104), Kf is If(003) / If(104), and 10≦Kf≦20. For example, Kf may be any value of 10, 11, 12, 13, 13.3, 13.5, 13.7, 14, 14.5, 14.7, 15, 15.3, 15.5, 15.7, 16, 16.3, 16.5, 16.7, 17, 17.5, 18, 19, 20, or a range value consisting of any two of these values.
[0058] The ratio Kf reflects the preferred orientation of the positive electrode active material in the positive electrode mixture layer. If the ratio is ≧20, it indicates that the preferred orientation is serious, that is, significant slippage occurs in the crystal plane of the positive electrode active material during the manufacturing process of the positive electrode mixture layer. Such slippage leads to cracks on the surface of the positive electrode particles, the stability of the material is low, and metal dissolution and side reactions with the interface are likely to occur. In addition, the larger the Kf, the closer the angle between the desorption direction of lithium ions and the direction of the electric field is to 90°, which is unfavorable to the desorption of lithium ions and reduces the charging ability of the battery. If the ratio Kf≦10, the adhesion effect between the positive electrode powder and the conductive agent is low, so the internal resistance of the battery is high, and the ohmic polarization of the lithium ion battery is large during the charging process, reducing the charging ability of the battery.
[0059] In some embodiments of the present invention, 13≦Kf≦17. When Kf is in this range, the orientation of the positive electrode active material in the positive electrode mixture layer is distributed within a more appropriate range, resulting in better charging capacity of the battery.
[0060] In some embodiments of the invention, 6≦Kf / Kc≦20. For example, Kf / Kc can be any value of 6, 7, 8, 8.5, 9, 9.3, 9.5, 9.7, 10, 10.3, 10.5, 10.7, 11, 11.3, 11.5, 11.7, 12, 12.5, 13, 13.5, 13.7, 14, 14.5, 14.7, 15, 15.5, 16, 17, 19, 20, or a range consisting of any two of these values.
[0061] Kf / Kc further indicates the preferred orientation of the positive electrode active material in the positive electrode mixture layer, and the higher the Kf / Kc, the higher the proportion of positive electrode active material particles in which the (003) crystal plane is parallel to the substrate plane. For fast charging batteries, the lithium absorption capacity of the negative electrode material is a determining factor that limits the charging capacity of the material, and appropriately reducing the kinetics of the positive electrode active material is favorable to improving the charging capacity of the entire battery and reducing the safety risk caused by lithium precipitation in the battery. Increasing the Kf / Kc of the positive electrode active material particles makes the movement direction of more lithium ions in the positive electrode active material particles parallel to the direction of the electric field inside the battery, making it difficult for lithium ions to be desorbed from the positive electrode, which is favorable for the absorption of negative electrode lithium ions. However, if the Kf / Kc is too high, the polarization of the lithium ion battery becomes large during the fast charging process, the rate of temperature rise due to charging increases, and the reaction with the electrolyte becomes intense, which destroys the structure of the positive electrode active material. Therefore, it is preferable that Kf / Kc is within the range of 6 to 20.
[0062] In some embodiments of the present invention, 8≦Kf / Kc≦14. When Kf / Kc is within this range, the proportion of positive electrode active material particles whose (003) crystal plane is parallel to the substrate plane is within a suitable range, which can ensure that the battery has excellent charging ability and the polarization of the battery is within a suitable range, so that the battery has better overall performance.
[0063] In the particles formed by the positive electrode active material in the positive electrode mixture layer, the ratio of the number of particles having a size of 1 μm to 3 μm to the total number of particles is greater than 60%, and may be any value selected from the group consisting of 61%, 63%, 65%, 67%, 70%, 73%, 75%, 78%, 80%, 83%, 85%, 87%, and 90%, or a range consisting of any two of these values.
[0064] The size uniformity of the positive electrode active material particles in the positive electrode mixture layer has a significant effect on the charging performance of the battery. The more uniform the size of the positive electrode active material particles in the positive electrode mixture layer, the smaller the difference in current density between different active particles of the positive electrode active material under high current charging conditions, i.e., the more consistent the delithiation degree between different particles is, which indicates a decrease in polarization, and further reduces the rate of temperature increase of the battery, ensuring that the battery has excellent charging ability and service life.
[0065] Example 1 (1) Manufacturing of positive electrode active material In step 1, the positive electrode active material precursor Ni 0.52 Co 0.045 Mn 0.435 (OH)2 and lithium carbonate are added to a mixer and mixed thoroughly to provide a lithium to precursor molar ratio of lithium carbonate of 1.04:1.
[0066] In step 2, the mixed material is put into an atmosphere furnace for sintering, and the sintering time in the heating region is 6 hours. The sintering temperature in the constant temperature region is 990°C, the sintering time in the constant temperature region is 12 hours, the atmosphere in the constant temperature region during the sintering process is an oxygen atmosphere, and the oxygen concentration in the constant temperature region of the atmosphere furnace is 30%.
[0067] In step 3, the positive electrode active material obtained after sintering is subjected to roller pulverization and then air current pulverization.
[0068] In step 4, the ground positive electrode active material is put into a high-speed mixer and mixed, the frequency of the mixer is set to 40 Hz, and the mixing time is set to 20 min.
[0069] In step 5, the mixed positive electrode active material is put into a kiln for secondary sintering to obtain the finished positive electrode active material. The sintering temperature is 550°C and the sintering time is 6 hours.
[0070] The half width at half maximum FWHW(003) of the (003) peak of the synthesized positive electrode active material is 0.088°, and the half width at half maximum FWHW(104) of the (104) peak is 0.097°. The peak area of the (003) peak of the synthesized positive electrode active material is Ic(003), and the peak area of the (104) peak is Ic(104), where Kc=Ic(003) / Ic(104) and Kc=1.66.
[0071] (2) Manufacturing of positive electrodes In step 1, the positive electrode active material, polyvinylidene fluoride as an adhesive, acetylene black as a conductive agent, and carbon nanotubes as a conductive agent are thoroughly mixed in a mass ratio of 97:1.5:1:0.5, N-methylpyrrolidone (NMP) is added, and the mixture is uniformly stirred under the action of a stirrer to obtain a positive electrode slurry in which the positive electrode active material, the adhesive, and the conductive agent are uniformly dispersed. The positive electrode slurry is then uniformly applied to an aluminum foil having a thickness of 12 μm, and the positive electrode slurry is applied on one side and then applied on the other side, so that the coating surface density on one side, minus the weight of the aluminum foil, is 16 mg / cm. 2 Let us assume that.
[0072] In step 2, the coated electrode plate is dried in an oven at 100°C to 130°C.
[0073] In step 3, the dried electrode plate is roll-pressed, and an X-ray diffraction test is performed on the positive electrode mixture layer by controlling the pressure and speed of the roll press, the temperature of the roll rod, and the number of times of the roll press. The peak area of the (003) peak of the positive electrode mixture layer is If(003), the peak area of the (104) peak of the positive electrode mixture layer is If(104), and Kf=If(003) / If(104), where Kf=15.74.
[0074] (3) Manufacturing of negative electrodes The negative electrode active material, sodium carboxymethylcellulose as a thickener, styrene butadiene rubber as a binder, and acetylene black as a conductive agent were mixed in a mass ratio of 96:0.8:1.2:2, deionized water was added, and the negative electrode active material, sodium carboxymethylcellulose as a thickener, styrene butadiene rubber as a binder, and acetylene black as a conductive agent were uniformly dispersed under the action of a stirrer to obtain a negative electrode slurry. The negative electrode slurry was then uniformly applied to copper foil of a certain thickness, and the surface density on one side, excluding the aluminum foil, was 7.37 mg / cm. 2 The coated electrode plate is then transferred to an oven at 100°C to 120°C to dry, and the same surface density is applied to the other side of the electrode plate, after which the plate is cold pressed and slit to obtain a negative electrode plate.
[0075] (4) Manufacturing of electrolyte The organic solvent is a mixture of ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) in a mass ratio of 1:1:1. The lithium salt LiPF6 is dissolved in the organic solvent and mixed uniformly to obtain the electrolyte. The concentration of the lithium salt is 1.0 mol / L.
[0076] (5) Separator manufacturing A polyethylene separator with a thickness of 12 μm is used.
[0077] (6) Battery manufacturing A positive electrode plate, a separator, and a negative electrode plate are stacked in this order, with the separator positioned between the positive and negative electrodes to play the role of isolation. The resulting cell is wound into a rectangular bare cell, which is then inserted into an external packaging. The cell is then baked to remove water, and a corresponding non-aqueous electrolyte is injected. The cell is then sealed, and the process of standing, hot and cold pressing, chemical formation, capacity selection, etc. is carried out to obtain a finished battery.
[0078] Example 2 In step 1 of the manufacturing process for the cathode active material, the precursor is Ni 0.78 Co 0.03 Mn 0.19(OH)2, the lithium salt is lithium hydroxide, and in step 2, the sintering temperature is 910°C, except that the other steps are completely identical to those in Example 1.
[0079] Example 3 In step 1 of the manufacturing process for the cathode active material, the precursor is Ni 0.55 Co 0.12 Mn 0.33 (OH)2, and in step 2, the sintering temperature in the constant temperature region is set to 945°C, and the other steps are the same as those in Example 1.
[0080] Example 4 In step 1 of the manufacturing process for the cathode active material, the precursor is Ni 0.60 Co 0.10 Mn 0.30 Except for (OH)2, the other steps are the same as those in Example 3.
[0081] Example 5 In step 1 of the method for producing the positive electrode active material, a zirconium oxide additive is added, which accounts for 0.4% of the total molar amount of metal elements other than lithium in the positive electrode active material, and the other steps are the same as those in Example 4.
[0082] Example 6 In step 1 of the method for producing the positive electrode active material, a zirconium oxide additive is added, which accounts for 2.9% of the total molar amount of metal elements other than lithium in the positive electrode active material, and the other steps are the same as those in Example 4.
[0083] Example 7 In step 1 of the method for producing a positive electrode active material, a zirconium oxide additive accounting for 0.4% of the total molar amount of metal elements other than lithium in the positive electrode active material is added, and in step 4, the ground positive electrode active material and an aluminum oxide additive accounting for 0.5% of the total molar amount of metal elements other than lithium in the positive electrode active material are thoroughly mixed. The other steps are the same as those in Example 4.
[0084] Example 8 In step 1 of the method for producing a positive electrode active material, a zirconium oxide additive accounting for 0.4% of the total molar amount of metal elements other than lithium in the positive electrode active material and a strontium oxide additive accounting for 0.1% are added, and in step 4, the ground positive electrode active material and an aluminum oxide additive accounting for 0.5% of the total molar amount of metal elements other than lithium in the positive electrode active material are thoroughly mixed. The other steps are the same as those in Example 4.
[0085] Example 9 In step 1 of the method for producing a positive electrode active material, a zirconium oxide additive accounting for 0.4% of the total molar amount of metal elements other than lithium in the positive electrode active material and a strontium oxide additive accounting for 0.1% are added, and in step 4, the ground positive electrode active material, an aluminum oxide additive accounting for 0.5% of the total molar amount of metal elements other than lithium in the positive electrode active material, and a tungsten oxide additive accounting for 0.2% are thoroughly mixed. The other steps are the same as those in Example 4.
[0086] Example 10 In step 1 of the manufacturing process for the cathode active material, the precursor is Ni 0.58 Co 0.14 Mn 0.28 In step 3, the positive electrode active material is thoroughly mixed with an aluminum oxide additive that accounts for 0.4% of the total molar amount of metal elements other than lithium in the positive electrode active material, and a titanium oxide additive that accounts for 0.2% of the total molar amount of metal elements other than lithium in the positive electrode active material. The other steps are the same as those in Example 4.
[0087] Example 11 In step 1 of the manufacturing process for the cathode active material, the precursor is Ni 0.635 Co 0.09 Mn 0.275In step 3, the positive electrode active material is sufficiently mixed with an aluminum oxide additive accounting for 0.9% of the total molar amount of metal elements other than lithium in the positive electrode active material, and a tungsten oxide additive accounting for 0.1% of the total molar amount of metal elements other than lithium in the positive electrode active material. The other steps are the same as those in Example 4.
[0088] Example 12 In step 1 of the manufacturing process for the cathode active material, the precursor is Ni 0.68 Co 0.09 Mn 0.27 The formula is (OH)2, the lithium salt is lithium hydroxide, and a zirconium oxide additive accounting for 0.3% of the total molar amount of metal elements other than lithium in the positive electrode active material, a strontium oxide additive accounting for 0.1%, and a barium oxide additive accounting for 0.1% are added; in step 2, the sintering temperature in the constant temperature region is set to 935°C; and in step 4, the pulverized positive electrode active material, an aluminum oxide additive accounting for 1.1% of the total molar amount of metal elements other than lithium in the positive electrode active material, and a tungsten oxide additive accounting for 0.2% are thoroughly mixed. Other steps are the same as those in Example 4.
[0089] Example 13 In step 1 of the manufacturing process for the cathode active material, the precursor is Ni 0.72 Co 0.05 Mn 0.23 The formula is (OH)2, the lithium salt is lithium hydroxide, a zirconium oxide additive accounting for 0.3% of the total molar amount of metal elements other than lithium in the positive electrode active material, a strontium oxide additive accounting for 0.1%, and a barium oxide additive accounting for 0.1% are added, in step 2, the sintering temperature in the constant temperature region is 910°C, and in step 4, the pulverized positive electrode active material, an aluminum oxide additive accounting for 0.7% of the total molar amount of metal elements other than lithium in the positive electrode active material, and a tungsten oxide additive accounting for 0.2% are thoroughly mixed, and the other steps are the same as those in Example 4.
[0090] Example 14 In step 1 of the method for producing a positive electrode active material, a zirconium oxide additive accounting for 0.15% of the total molar amount of metal elements other than lithium in the positive electrode active material and a strontium oxide additive accounting for 0.75% are added, and in step 4, the ground positive electrode active material and an aluminum oxide additive accounting for 0.1% of the total molar amount of metal elements other than lithium in the positive electrode active material are thoroughly mixed. The other steps are the same as those in Example 4.
[0091] Example 15 In step 2 of the method for producing a positive electrode active material, the sintering temperature in the constant temperature region is 980° C., and the sintering time in the constant temperature region is 24 hours, but the other steps are the same as those in Example 9.
[0092] Example 16 In step 2 of the method for producing a positive electrode active material, the sintering temperature in the constant temperature region is 925° C., and the sintering time in the constant temperature region is 7 hours, but the other steps are the same as those in Example 9.
[0093] Example 17 In step 2 of the method for producing the positive electrode active material, the sintering temperature in the constant temperature region is 980°C, and the sintering time in the constant temperature region is 24 hours. In step 3, the grinding parameters are adjusted, and the other steps are the same as those in Example 9.
[0094] Examples 18 to 21 In step 3 of the manufacturing method of the positive electrode plate, other than adjusting the roll press parameters, the other steps are the same as those in Example 15.
[0095] Comparative Example 1 In step 1 of the manufacturing process for the cathode active material, the precursor is Ni 0.46 Co 0.04 Mn 0.50 Except for (OH)2, the other steps are the same as in Example 1.
[0096] Comparative Example 2 In step 1 of the manufacturing process for the cathode active material, the precursor is Ni 0.60 Co 0.03 Mn 0.37 Except for (OH)2, the other steps are the same as in Example 1.
[0097] Comparative Example 3 In step 1 of the manufacturing process for the cathode active material, the precursor is Ni 0.82 Co 0.03 Mn 0.15 The other steps are the same as those in Example 1, except that the lithium salt is lithium hydroxide.
[0098] Specific experimental parameters and the electrochemical performance of the batteries in Examples 1 to 21 and Comparative Examples 1 to 3 are shown in Tables 1, 2 and 3.
[0099] The test methods for the parameters relating to the positive electrode active material and the material of the mixture layer in Tables 1 and 2 are as follows.
[0100] 1. The test method for the full width at half maximum (FWHW(003)) of the (003) diffraction peak of the positive electrode active material powder and the full width at half maximum (FWHW(104)) of the (104) diffraction peak of the positive electrode active material powder is as follows.
[0101] The half-width FWHW(003) of the (003) diffraction peak of the positive electrode active material powder and the half-width FWHW(104) of the (104) diffraction peak of the positive electrode active material powder are obtained using an X-ray powder diffractometer (X'pert PRO) in accordance with the X-ray diffraction analysis method general rules JIS K 0131-1996, and the X-ray diffraction pattern is obtained and the background and Kα2 of the X-ray diffraction pattern are subtracted. FWHW(003) is the peak width at the position of half the height of the (003) characteristic diffraction peak, and FWHW(104) is the peak width at the position of half the height of the (104) characteristic diffraction peak, and the unit is °.
[0102] 2. The test method for the ratio Kc of the peak area Ic(003) of the (003) diffraction peak of the positive electrode active material to the peak area Ic(104) of the (104) diffraction peak of the positive electrode active material is as follows.
[0103] The Kc value of the positive electrode active material powder is obtained using an X-ray powder diffractometer (X'pert PRO) in accordance with JIS K 0131-1996, a general rule for X-ray diffraction analysis, and an X-ray diffraction pattern is obtained, where Kc=I(003) / I(104), where I(003) is the peak area of the (003) characteristic diffraction peak, and I(104) is the peak area of the (104) characteristic diffraction peak. Specifically, the method for testing the Kc value of the positive electrode active material powder is to place a certain mass of the positive electrode active material powder in the X-ray powder diffractometer, obtain the peak area of the (003) crystal plane diffraction peak and the peak area of the (104) crystal plane diffraction peak by X-ray diffraction analysis, and further obtain the Kc value of the positive electrode active material powder.
[0104] 3. The test method for the ratio Kc of the peak area Ic(003) of the (003) diffraction peak of the positive electrode mixture layer to the peak area Ic(104) of the (104) diffraction peak of the positive electrode mixture layer is as follows.
[0105] The Kf value of the positive electrode mixture layer is obtained using an X-ray powder diffractometer (X'pert PRO) in accordance with the X-ray diffraction analysis general rules JIS K 0131-1996, and an X-ray diffraction pattern is obtained, where Kc = I(003) / I(104), where I(003) is the peak area of the (003) characteristic diffraction peak, and I(104) is the peak area of the (104) characteristic diffraction peak. Specifically, the test method for the Kf value of the positive electrode mixture layer is to place the positive electrode plate directly into the X-ray powder diffractometer, obtain the peak area of the (003) crystal plane diffraction peak and the peak area of the (104) crystal plane diffraction peak by X-ray diffraction analysis, and further obtain the Kf value of the positive electrode mixture layer powder.
[0106] The test methods for the electrochemical performance of the batteries in Table 3 are as follows.
[0107] 1. Testing the gram capacity of the positive electrode active material In a test environment of 25°C±3°C, the lithium ion batteries prepared in the examples and comparative examples were charged to 4.35V at 1 / 3C rate and discharged to 2.80V at 1 / 3C rate, and the discharge capacity was recorded. The discharge capacity was divided by the mass of the active material in the positive plate to obtain the gram capacity of the positive active material. The higher the gram capacity of the positive active material, the higher the energy density that the battery can provide, indicating better battery performance.
[0108] 2. Battery capacity retention test after 1000 cycles At 25°C±3°C, the lithium ion batteries prepared in the examples and comparative examples were charged to 4.35V at 1C rate and discharged to 2.80V at 1C rate for 1000 charge / discharge cycles, and the charge and discharge capacities per cycle were recorded. The ratio of the discharge capacity at the 1000th cycle to the discharge capacity at the first cycle is the capacity retention rate of the battery after 1000 cycles. The higher the capacity retention rate of the battery after cycling, the stronger the capacity fade resistance ability of the battery and the better the performance of the battery.
[0109] 3. Testing the total amount of Mn ions and Ni ions dissolved from the negative electrode plate of the battery after 1000 cycles The lithium ion batteries prepared in the examples and comparative examples were charged to 4.35V at 1C rate and discharged to 2.80V at 1C rate for 1000 charge-discharge cycles, then discharged to 2.80V at 1C rate, and disassembled. The negative plate of the battery was taken out and immersed in DMC for 12 hours to remove impurities remaining on the surface of the negative plate, and then baked in an oven at 80°C for 2 hours to remove DMC and remaining electrolyte. Then, the Mn element content and Ni element content of the negative plate were tested using EPA6010D inductively coupled plasma atomic emission spectroscopy, and the sum of the two contents is the total amount of Mn ions and Ni ions dissolved in the negative plate of the battery after 1000 cycles. The lower the total amount of Mn ions and Ni ions dissolved in the negative plate, the more stable the structure of the positive electrode material is, and the longer the service life of the battery is accordingly.
[0110] 4. Testing the increase in battery impedance after 1000 cycles At 25°C ± 2°C, the lithium ion batteries manufactured in the examples and comparative examples are discharged to 2.8V at 1C rate, charged to 4.35V at 1C rate, and further discharged to 2.8V at 1C rate, and the discharge capacity C1 is recorded. The lithium ion batteries manufactured are further charged to 4.35V at 1C1 current, discharged at 1C1 current for 30 minutes, and then left to stand for 180 minutes, and the voltage V1 of the battery after standing is recorded, and further discharged at 5C1 current for 10 seconds, and the terminal voltage V2 after the voltage discharge for 10 seconds is recorded, and the initial impedance R1 = (V2 - V1) / 5C1. The manufactured lithium ion batteries are charged to 4.35V at 1C rate, and discharged to 2.80V at 1C rate for 1000 charge and discharge cycles. Then, the battery after 1000 cycles is discharged to 2.8V at a rate of 1C1, charged to 4.35V at a rate of 1C1, and discharged to 2.8V at a rate of 1C1 again, and the discharge capacity C2 is recorded. The lithium-ion battery thus manufactured is charged to 4.35V at a current of 1C2, and then discharged at a current of 1C2 for 30 minutes, and then left to stand for 180 minutes, and the voltage V3 of the battery after standing is recorded, and the battery is discharged at a current of 5C2 for 10 seconds, and the terminal voltage V4 after the voltage discharge for 10 seconds is recorded, and the impedance after 1000 cycles is R2=(V4-V3) / 5C2. The impedance increase after 1000 cycles is ΔR=(R2-R1) / R1. The lower the impedance increase of the battery after 1000 cycles, the lower the attenuation of the charging ability during the use of the battery, that is, it indicates that the battery has better charging ability. TIFF2025501057000001.tif250170TIFF2025501057000002.tif250170TIFF2025501057000003.tif27170TIFF20255010570 00004.tif249170TIFF2025501057000005.tif174170TIFF2025501057000006.tif250170TIFF2025501057000007.tif117170
[0111] From the data in Tables 1, 2 and 3, the following conclusions can be drawn:
[0112] Comparing Example 1 with Comparative Example 1 and Comparative Example 2, the capacity retention rate after 1000 cycles of the battery manufactured in Example 1 is 83.1%, which is higher than 61.2% of Comparative Example 1 and 66.1% of Comparative Example 2, which indicates that the battery manufactured in Example 1 has better cycle stability; the impedance increase rate after 1000 cycles of the battery manufactured in Example 1 is 35.2%, which is lower than 92.6% of Comparative Example 1 and 86.5% of Comparative Example 2, which indicates that the battery manufactured in Example 1 has better power decay resistance performance; the excellent performance of Example 1 is obtained by lowering the total amount of Mn ions and Ni ions eluted from the positive electrode active material through the design of the molar content of cobalt and manganese. The total amount of Mn ions and Ni ions eluted from the negative electrode plate after 1000 cycles of the battery manufactured in Example 1 is 342.1 ppm, which is much lower than 667.3 ppm of Comparative Example 1 and 607.9 ppm of Comparative Example 2.
[0113] Comparing Example 2 and Comparative Example 3, the capacity retention rate after 1000 cycles of the battery manufactured in Example 2 is 77.5%, which is higher than 34.2% of Comparative Example 3, which indicates that the battery manufactured in Example 2 has better cycle stability, the impedance increase rate after 1000 cycles of the battery manufactured in Example 2 is 42.3%, which is lower than 126.8% of Comparative Example 3, which indicates that the battery manufactured in Example 2 has better power decay resistance performance, and the excellent performance of Example 2 is obtained by lowering the total amount of Mn ions and Ni ions dissolved from the positive electrode active material through the design of the molar content of cobalt and manganese. The total amount of Mn ions and Ni ions dissolved from the negative electrode plate after 1000 cycles of the battery manufactured in Example 2 is 421.7 ppm, which is much lower than 826.3 ppm of Comparative Example 3.
[0114] Comparing Example 1 and Example 3, the capacity retention rate after 1000 cycles of the battery manufactured in Example 3 is 84.3%, which is higher than 83.1% of Example 1, indicating that the battery manufactured in Example 3 has better cycle stability, the impedance increase rate after 1000 cycles of the battery manufactured in Example 3 is 28.7%, which is lower than 35.2% of Example 1, indicating that the battery manufactured in Example 3 has better power decay resistance performance, and the excellent performance of Example 3 is obtained by lowering the total amount of Mn ions and Ni ions eluted from the positive electrode active material through better design of the molar contents of cobalt and manganese. The total amount of Mn ions and Ni ions eluted from the negative electrode plate after 1000 cycles of the battery manufactured in Example 3 is 285.5 ppm, which is lower than 342.1 ppm of Example 1.
[0115] Comparing Example 5 and Example 4, the capacity retention rate after 1000 cycles of the battery manufactured in Example 5 is 88.6%, which is higher than 86.5% of Example 4, which indicates that the battery manufactured in Example 5 has better cycle stability, the impedance increase after 1000 cycles of the battery manufactured in Example 5 is 25.1%, which is lower than 31.3% of Example 4, which indicates that the battery manufactured in Example 3 has better power decay resistance performance, and the excellent performance of Example 5 is obtained by improving the structural stability of the material by introducing an appropriate amount of additive element Zr, and lowering the total amount of elution of Mn ions and Ni ions of the positive electrode active material. The total amount of elution of Mn ions and Ni ions of the negative electrode plate after 1000 cycles of the battery manufactured in Example 5 is 241.3 ppm, which is lower than 292.0 ppm of Example 4.
[0116] Comparing Example 6 with Example 5, the positive electrode gram capacity of the battery prepared in Example 6 is 178.6 mAh / g, which is much lower than 186.5 mAh / g of Example 5, which indicates that the excessive addition of Zr element affects the energy density of the battery.
[0117] Comparing Example 7 and Example 5, the capacity retention rate after 1000 cycles of the battery manufactured in Example 7 is 93.7%, which is higher than 88.6% of Example 5, which indicates that the battery manufactured in Example 7 has better cycle stability; the impedance increase after 1000 cycles of the battery manufactured in Example 7 is 16.7%, which is lower than 25.1% of Example 5, which indicates that the battery manufactured in Example 7 has better power decay resistance performance; the excellent performance of Example 7 is obtained by co-introducing the appropriate amount of additive elements Zr and Al to improve the structural stability of the material and lower the total amount of Mn ions and Ni ions dissolved in the positive electrode active material. The total amount of Mn ions and Ni ions dissolved in the negative electrode plate after 1000 cycles of the battery manufactured in Example 7 is 191.4 ppm, which is lower than 241.3 ppm of Example 5.
[0118] Comparing Example 8, Example 9, and Example 10 with Example 7, the capacity retention rates after 1000 cycles of the batteries manufactured in Examples 8, 9, and 10 are 94.9%, 96.2%, and 95.8%, respectively, which are higher than 93.7% of Example 7, which indicates that the batteries manufactured in Examples 8, 9, and 10 have better cycle stability. The impedance increase rates after 1000 cycles of the batteries manufactured in Examples 8, 9, and 10 are 12.6%, 6.8%, and 10.7%, respectively, which are lower than 16.7% of Example 7, which indicates that the batteries manufactured in Examples 8, 9, and 10 have better power decay resistance performance. The excellent performance of Examples 8, 9, and 10 is obtained by further improving the structural stability of the material by selectively adding Ti, Sr, and W elements in addition to the joint introduction of the appropriate amount of additive elements Zr and Al, and by further reducing the total amount of elution of Mn ions and Ni ions of the positive electrode active material. The total amounts of Mn ions and Ni ions dissolved from the negative plates of the batteries manufactured in Examples 8, 9 and 10 after 1000 cycles were 153.7 ppm, 126.1 ppm and 137.4 ppm, respectively, which were lower than 191.4 ppm in Example 7.
[0119] Examples 11, 12 and 13 further show that the battery manufactured with the positive electrode active material synthesized by designing the molar ratio of cobalt and manganese, and the type and content of additive elements has high positive electrode material gram capacity, high capacity retention rate and better power decay resistance performance. The positive electrode gram capacity of Examples 11, 12 and 13 is 190.7mAh / g, 196.4mAh / g and 196.1mAh / g, respectively, the capacity retention rate after 1000 cycles is 92.5%, 92.1% and 91.5%, respectively, and the impedance increase rate after 1000 cycles is 14.5%, 13.8% and 16.7%, respectively.
[0120] Comparing Example 14 and Example 8, the capacity retention rate after 1000 cycles of the battery manufactured in Example 8 is 94.9%, which is higher than 87.3% of Example 14, which indicates that the battery manufactured in Example 8 has better cycle stability, the impedance increase after 1000 cycles of the battery manufactured in Example 8 is 12.6%, which is lower than 25.1% of Example 1, which indicates that the battery manufactured in Example 8 has better power decay resistance performance, and the excellent performance of Example 8 is obtained by improving the structural stability of the material and lowering the total amount of Mn ions and Ni ions eluted from the positive electrode active material by introducing the added elements Zr and Al in an appropriate range. The total amount of Mn ions and Ni ions eluted from the negative electrode plate after 1000 cycles of the battery manufactured in Example 8 is 153.7 ppm, which is lower than 224.3 ppm of Example 5.
[0121] Comparing Example 15 and Example 9, the capacity retention rate after 1000 cycles of the battery manufactured in Example 9 is 96.2%, which is higher than 86.3% of Example 15, which indicates that the battery manufactured in Example 9 has better cycle stability; the impedance increase rate after 1000 cycles of the battery manufactured in Example 9 is 6.8%, which is lower than 35.5% of Example 15, which indicates that the battery manufactured in Example 9 has better power decay resistance performance; the excellent performance of Example 9 is obtained by improving the structural stability of the material through the appropriate design of FWHW(003) and FWHW(104) and lowering the total amount of Mn ions and Ni ions dissolved from the positive electrode active material. The total amount of Mn ions and Ni ions dissolved from the negative electrode plate after 1000 cycles of the battery manufactured in Example 9 is 126.1 ppm, which is lower than 273.5 ppm of Comparative Example 15. At the same time, if the FWHW(003) and FWHW(104) are too low, it indicates that the positive electrode active material particles grow too much, which leads to a decrease in kinetics and affects the gram capacity of the positive electrode active material. Comparing Example 15 with Example 9, the gram capacity of the positive electrode material of the battery prepared in Example 9 is 188.6 mAh / g, which is much higher than that of Example 15 (174.2 mAh / g).
[0122] Comparing Example 16 and Example 9, the capacity retention rate after 1000 cycles of the battery manufactured in Example 9 is 96.2%, which is higher than 87.9% of Example 16, which indicates that the battery manufactured in Example 9 has better cycle stability; the impedance increase rate after 1000 cycles of the battery manufactured in Example 9 is 6.8%, which is lower than 29.6% of Example 16, which indicates that the battery manufactured in Example 9 has better power decay resistance performance; the excellent performance of Example 9 is obtained by improving the structural stability of the material through the appropriate design of FWHW(003) and FWHW(104) and lowering the total amount of Mn ions and Ni ions dissolved in the positive electrode active material. The total amount of Mn ions and Ni ions dissolved in the negative electrode plate after 1000 cycles of the battery manufactured in Example 9 is 126.1 ppm, which is lower than 237.9 ppm of Example 16.
[0123] Comparing Examples 17 to 21 with Example 9, the capacity retention rate after 1000 cycles of the battery produced in Example 9 was 96.2%, which was higher than 77.6% of Example 17 and 81.5% of Example 18, indicating that the battery produced in Example 9 had better cycle stability. The impedance increase rate after 1000 cycles of the battery produced in Example 9 was 6.8%, which was lower than 38.8% of Example 17 and 32.3% of Example 18, indicating that the battery produced in Example 9 had better power decay resistance performance. The excellent performance of Example 9 was achieved by appropriately designing the Kc value of the positive electrode active material and the Kf value of the positive electrode mixture layer to reduce the total amount of eluted Mn ions and Ni ions of the positive electrode active material. The total amount of eluted Mn ions and Ni ions from the negative electrode plate of the battery produced in Example 9 after 1000 cycles was 126.1 ppm, which is lower than 358.1 ppm in Example 17 and 235.8 ppm in Example 18.
[0124] The above step description is only to help understand the method, structure and central idea of the present invention. Those skilled in the art can make some improvements and modifications to the present invention without departing from the principle of the present invention, and these improvements and modifications also belong to the scope of the claims of the present invention.
[0125] [Industrial Applicability] The present invention provides the following advantageous technical effects:
[0126] 1. The dissolution of the transition metal elements nickel, manganese and cobalt in the positive electrode active material can be reduced, and the charging capacity, cycle life and safety performance of the battery can be improved. For the positive electrode active material, when the Ni content in the material is high, the lithium absorption and desorption degree of the positive electrode active material increases, the structural stability of the material is low, and the Mn content increases, the Mn dissolution is likely to destroy the surface protective film of the negative electrode, which leads to an increase in impedance, increases the risk of lithium precipitation, and reduces the charging capacity, cycle life and safety performance of the battery. By rationally designing the amount and composition of the added elements, the dissolution of metal ions during the use of the positive electrode active material can be suppressed, and the charging capacity, cycle life and safety performance of the battery can be improved.
[0127] 2. The positive electrode particles can reduce the microcracks that occur during the processing of the positive electrode plate, and ensure that the positive electrode has excellent charging ability, cycle life and safety performance. The appropriate ratio of the compression ratio of the positive electrode plate to the compression ratio of the positive electrode powder can ensure excellent electrical contact between the positive electrode active material particles, between the positive electrode active material particles and the conductive agent, and can reduce the number of slip cracks of the positive electrode active material particles. When the ratio of the compression ratio of the positive electrode plate to the compression ratio of the positive electrode powder is low, the electrical contact area between the positive electrode particles, between the positive electrode particles and the conductive agent is insufficient, and the ohmic internal impedance of the positive electrode mixture layer is large, which affects the charging performance of the battery; when the ratio of the compression ratio of the positive electrode plate to the compression ratio of the positive electrode powder is high, the compression ratio of the positive electrode mixture layer is high, which is likely to cause the positive electrode active material particles to form slip cracks, which leads to the deterioration of the electrolyte and the elution of transition metals, which affects the charging ability, cycle life and safety performance.
Claims
1. A positive electrode active material comprising lithium nickel cobalt manganese oxide, In the lithium nickel cobalt manganese oxide, when the total molar amount of nickel, cobalt, and manganese is taken as 100%, the molar amount of manganese is taken as m % and the molar amount of cobalt is taken as n %, and the conditions 20<n+m<50 and 0.1<n / m<0.6 are satisfied; the half width at half maximum of a (003) peak of the positive electrode active material is taken as FWHW(003) and the half width at half maximum of a (104) peak of the positive electrode active material is taken as FWHW(104), and FWHW(003) and FWHW(104) satisfy 0.4≦FWHW(003) / FWHW(104)≦2.
0.
2. m and n are (i) 19≦m<43.5, (ii) 3.0≦n≦12, and (iii) The positive electrode active material according to claim 1, which satisfies any one of 0.10≦n / m≦0.
502.
3. The alloy further includes an M element, the M element including a Zr element and at least one of Al, Mg, Ti, Y, Sr, Y, Mo, Nb, Sn, Ba, La, Ce, and W elements; 3. The positive electrode active material according to claim 1, wherein the percentage of the molar amount of M element and the total molar amount of nickel, cobalt, and manganese is x %, where x % is a percentage of 0.1≦x≦2.5, where x % is a percentage of the total molar amount of nickel, cobalt, and manganese, when the total molar amount of nickel, cobalt, and manganese is 100%.
4. The M element includes Zr, Al, and at least one of Mg, Ti, Y, Sr, Y, Mo, Nb, Sn, Ba, La, Ce, and W, the molar content of the M element is x%, the molar content of the Zr element is x1%, and the molar content of the Al element is x2%, and x, x1, and x2 are each independently: (iv) 0.20≦x1≦0.45, (v) 0.15≦x2≦1.5, (vi) 0.2≦x1 / x2≦1, and (vii) The positive electrode active material according to claim 3, which satisfies any one of 0<(x-x1-x2) / x<0.
5.
5. The half width of the (003) peak of the positive electrode active material is defined as FWHW(003), and the half width of the (104) peak of the positive electrode active material is defined as FWHW(104), The range of FWHW(003) is 0.06° to 0.15°; The positive electrode active material according to claim 1 or 2, wherein the FWHW(104) is in the range of 0.06° to 0.15°.
6. 3. The positive electrode active material according to claim 1, wherein a peak area of a (003) peak of the positive electrode active material is Ic(003), a peak area of a (104) peak is Ic(104), and Kc is Ic(003) / Ic(104), where 1≦Kc≦2.
7. Li a Ni b Co m/100 Mn n/100 M x/100 O 2 4. The cathode active material of claim 3, wherein 0.80≦a≦1.10, 0.4<b<0.8, 20<n+m<50, 0.1<n / m<0.6, 0.1≦x≦2.5, and M comprises Zr and at least one of Al, Mg, Ti, Y, Sr, Y, Mo, Nb, Sn, Ba, La, Ce, and W.
8. A secondary battery including a positive electrode, The positive electrode includes a positive electrode current collector and a positive electrode mixture layer provided on the positive electrode current collector, and the positive electrode mixture layer includes the positive electrode active material according to claim 1 .
9. 9. The secondary battery according to claim 8, wherein a peak area of a (003) peak of the positive electrode mixture layer is If(003), a peak area of a (104) peak is If(104), Kf is If(003) / If(104), and 10≦Kf≦20.
10. 9. The secondary battery according to claim 8, wherein a peak area of a (003) peak of the positive electrode mixture layer is If(003), a peak area of a (104) peak is If(104), Kf is If(003) / If(104), and 6≦Kf / Kc≦20.
11. 9. The secondary battery according to claim 8, wherein the ratio of the number of particles having a size of 1 μm to 3 μm to the total number of particles in the positive electrode mixture layer is greater than 60%.
12. A power consuming device comprising the secondary battery according to any one of claims 8 to 11.
Citation Information
Patent Citations
Ternary material and application thereof
CN114709413A
Low cobalt positive electrode active material, method for preparing same, electrochemical device, and electronic apparatus
CN114759183A
Positive electrode active material for lithium secondary battery, method for manufacturing same, lithium secondary battery electrode, lithium secondary battery, and electric storage device
WO2015049862A1